Juridical Analysis of the Imposition of Criminal Sanctions on Police Persons as Perpetrators of Narcotics Abuse in the Criminal Justice System in Indonesia - Ricky Adryan; Madiasa Ablisar; Edi Yunara; Idha Apriliyana (PT FORMOSA CENDEKIA GLOBAL, 2023)
Cases of drug abuse are of particular concern in Indonesia because they involve various groups, one of which is a member of the police. Every member of the police is a law enforcement officer. The problems to be studied here are law enforcement, the urgency of imposing criminal sanctions and the judge's consideration of the weighting of criminal sanctions against police officers as perpetrators of narcotics abuse. obtain primary, secondary and tertiary legal materials which will be analyzed qualitatively by drawing deductive conclusions. The conclusions obtained in this study include law enforcement against police officers as narcotics abusers can be carried out through the criminal justice system and enforcement of discipline and the Indonesian National Police's code of ethics.